Kalibrasi Instrumen Literasi Matematika Siswa Menggunakan IRT dan Aplikasinya untuk Estimasi Skor - Susanto, Hari Purnomo; Retnawati, Heri (Edumatica : Jurnal Pendidikan Matematika, 2023)
Mathematical literacy is one of the components that is of concern to the Minimum Competency Assessment (AKM). This policy is an effort by the Ministry of Education and Culture to overcome the low literacy skills of students, and the faktors that cause it. Multistage Adaptive Test (MSAT) is used as an assessment method in AKM. The MSAT was developed with the IRT concept. The purpose of this article is to apply Item Respons Theory (IRT) to calibrate mathematical literacy instrumens and utilize the calibration result item parameters to estimate scores for mathematical literacy skills. Many items in the instrumen used are 15 multiple choice items. Respondents were used as many as 66 grade 8 junior high school students. After going through the construct validation process using Confirmatory Factor Analysis (CFA), 2 items did not meet, because they had a low loading factor, and 13 items were used for the calibration process. The grain calibration and scoring processes were carried out using the R package Mirt program. The calibration results show that the instrument matches the Rasch model. All assumptions of unidimensional IRT are proven to be met, so there is no violation in estimating item parameters. The item parameter is the level of difficulty where there is one item that does not fit, namely item 3. The intersection of the information function and the standard error shows that the instrument will provide accurate information if it is used by students with abilities of -2.965 to 1.085. The resulting item parameters can be used to estimate the algebra content math literacy score.